PENGARUH PEMOTONGAN TUNJANGAN SELAMA MASA PANDEMI COVID 19 TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING DI PERUM LEMBAGA PENYELENGGARA PELAYANAN NAVIGASI PENERBANGAN INDONESIA (LPPNPI) CABANG PALEMBANG - M Kukuh Dharma Utama (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This study examines the effect of cutting allowances on employees and wants to analyze the effect of cutting allowances on performance with motivation as an intervening variable at Perum LPPNPI Palembang Branch. By using saturated sampling technique obtained a sample of 36 respondents. The research method in this study used descriptive research with a quantitative approach. The effects of the Covid-19 pandemic that have spread throughout the world have had a profound impact on the economic sector. The negative impact even affects most companies, both large, medium, and small. State-owned enterprises (State Owned Enterprises) have an impact that is not much different if this situation is not resolved immediately, employees will experience financial losses. In the field, it is often found that every day workers do the opposite and can pose a danger to the company itself. Perum LPPNPI Palembang Branch is one of the state-owned companies as the only company engaged in flight navigation services in Indonesia, it is necessary to pay attention to factors that can affect performance, one of which is allowances. This shows that the variable withholding allowances has a significant effect on the performance of the Palembang branch of Perum LPPNPI Indonesia. With the cut in allowances, it will definitely have an impact on the family life of employees, this decrease in income will certainly greatly disrupt family finances because on the other hand, the value of the elements of family expenditure also increases.